Electroluminescence studies on europium (dibenzoylmethane)3 bathophenanthroline. - Ho, San San. (2011)
Lanthanide metal compounds such as Europium (Dibenzoylmethanato)3 Bathophenanthroline (Eu(DBM)3Bath) has been of interest in Organic Light Emitting Diode (OLED) application due to their characteristic sharp peak emission. OLEDs always have the potential application for full color and flat panel displays, therefore much attention is placed in this field. However, a great part of organic materials shows broad emission spectra. Rare Earth ions such as Eu3+ is able to exhibit bright and spectrally narrow red emission. In this work we report on the characteristic behaviors and the transition mechanism of Eu(DBM)3Bath. OLED devices involving Eu(DBM)3Bath as a emitting layer were fabricated and the process would be discussed. Several test on the emission properties of Eu(DBM)3Bath was also done. Future work and summary would be discussed at the end.